The origin of hydrocarbon gases in the South-East of Western Siberia (Russia) - Goncharov I. V. Ivan Vasilyevich; Korobochkina V. G.; Oblasov N. V.; Nosova S. V.; Samoilenko V. V. (2005, 2005)
В фонде НТБ ТПУ отсутствует